2017
DOI: 10.3390/f8070248
|View full text |Cite
|
Sign up to set email alerts
|

Soil Respiration Changes after Prescribed Fires in Spanish Black Pine (Pinus nigra Arn. ssp. salzmannii) Monospecific and Mixed Forest Stands

Abstract: Soil respiration is a major carbon pathway sensitive to environmental changes. Using prescribed burnings to reduce fuel accumulation and lower risks of large-scale wildfires has recently become more important. Prescribed burning can significantly alter the soil environment, but its effect in practice on soil respiration is not sufficiently understood. We evaluated the effects of prescribed burning on soil respiration before and after burning (May-July 2016). Prescribed burning was conducted in two natural pine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…In addition, emerged seedlings are also very easily detectable by the predators (including birds and rodents) in the absence of ground vegetation as it was observed in other studies (e.g. Sagra et al, 2017).…”
Section: Seedling Early Survivalsupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, emerged seedlings are also very easily detectable by the predators (including birds and rodents) in the absence of ground vegetation as it was observed in other studies (e.g. Sagra et al, 2017).…”
Section: Seedling Early Survivalsupporting
confidence: 74%
“…Similarly, Sagra et al (2018) reported that ash was a limiting factor on seed germination and seedling survival of P. pinaster in a field experiment. Such results could be explained by the alteration of soil properties after controlled burning in particular a reduced soil moisture and soil respiration and an increased soil temperature (Plaza-Álvarez et al, 2017).…”
Section: Germination and Seedling Emergencementioning
confidence: 99%
“…Thus in Mediterranean regions, prescribed burning is usually carried out in spring (early season) or autumn (late season) when the moisture of vegetation and soil is high to obtain low‐burn intensity, which implies low soil organic layer combustion (McNabb & Cromack jr, 1990; Úbeda, Pereira, & Badía, 2018). When the prescribed fire is performed under these humidity and temperature conditions, temporal changes in soil properties are usually limited to the short term (Catalanotti et al, 2018; Mataix‐Solera & Cerdà, 2009; Merino et al, 2019; Plaza‐Álvarez et al, 2017, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Microbiological and physico‐chemical soil properties have been widely used as soil quality indicators to evaluate fire‐induced changes and soil degradation (Lucas‐Borja et al, 2012; Úbeda, Alcañiz, Borges, Outeiro, & Francos, 2019). Some microbiological parameters, such as soil basal respiration, microbial biomass, and certain soil enzyme activities, have been used to quantify soil biological disturbance in relation to burn severity (García‐Orenes et al, 2017; Mabuhay, Nakagoshi, & Isagi, 2006; Moya et al, 2018; Plaza‐Álvarez et al, 2017). So, the enzymatic activities related to carbon, nitrogen, and phosphorus cycles, in addition to characteristic microbial indicators, such as soil respiration, have been proposed as indicators of soil functionality (Fontúrbel et al, 2012; Hedo, Lucas‐Borja, Wic, Andrés‐Abellán, & Las Heras, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation